Quantization Effects in TanDEM-X Data - Martone, Michele; Braeutigam, Benjamin; Krieger, Gerhard (IEEE Transactions on Geoscience and Remote Sensing, 2015)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurement) is an innovative space-borne bistatic synthetic aperture radar (SAR) system comprising the twin satellites TerraSAR-X and TanDEM-X. The primary objective of the mission is the generation of a worldwide, timely, and consistent digital elevation model (DEM) in bistatic SAR configuration with an unprecedented accuracy. For TanDEM-X, as well as for future space-borne SAR missions, an increasing volume of on-board data is going to be demanded. This is due to the employment of large bandwidths, high PRFs, and multiple polarizations, which implies inevitably hard requirements in terms of on-board memory and downlink capacity. In this scenario, SAR raw data quantization represents an essential aspect. The data rate employed for the digitization of the recorded radar signal affects both the amount of data to be stored and transmitted to the ground and the quality of the resulting SAR products. In this paper, the impact of quantization on TanDEM-X monostatic and interferometric data is evaluated. Key quantities in estimating interferometric and SAR performance, like coherence and phase errors, are investigated in detail. Based on the obtained results, an optimization of the resource allocation strategy for the global DEM acquisition of TanDEM-X is discussed.
DLR Import::2019-04-02
Keywords: Block-adaptive quantization (BAQ); SAR interferometry (InSAR); synthetic aperture radar (SAR); TerraSAR-X add-on for Digital Elevation Measurement (TanDEM-X) mission